Learning About Reproductive Health for Young Girls at Kartika Vocational School - Susilowati, Lilik; Nurlelawati, Ella; Siswosuharjo, Partono (Akademi Keperawatan RSPAD Gatot Soebroto, 2022)
This study aims to provide reproductive health education to young women related to the role of parents, friends, and the media. The research method used in this research is a cross-sectional survey method. The population in this study were all 121 Kartika Vocational School students. Samples were taken by means of total sampling, that is, the entire population was sampled. In this analysis it was found that descriptively regarding the knowledge variable, out of 121 respondents whose knowledge of reproductive health was not good was 78 people (64.5%), while respondents who had good knowledge about reproductive health were 43 people (35.5%). There were 92 people (76.0%) whose friends did not play a role, while the respondents whose friends played a role were 29 people (24.0%). 68 people (56.2%) their level of knowledge about reproductive health was not influenced by the role of the media, while 53 people (43.8%) had an influence by the role of the media.